Tourism Development Strategy of Mangrove Forest in the Village Langadai Kotabaru Hilir Subdistrict Kelumpang - Julianti, Erni (TROPICAL WETLAND JOURNAL, 2018)
The basic concept of tourism development strategy mangrove forest is reviewing the state of observation in the area of mangrove forests, perceptions and preferences of society and local government, and the use of SWOT analysis. This study aims to determine the development strategy of mangrove forest tour in the village Langadai Kelumpang Hilir Subdistrict, so mangrove well then expected to implement development programs and the development of an integrated strategy between the conservation of natural resouces with economic development in a sustainable society. The application of the concept of travel in the area of mangrove forest ecosystems in general is expected to reduce the rate of destruction of these areas by the public.            Processing method used is the analysis of the potensial landscape and strategy development SWOT analysis. Analysis of the data elements of the landscape each focal point of the model pengharkatan done that is by scoring according to the criteria assessment landscape elements that have been modified. While the SWOT analysis is a technique for identifying problems based on potential or strengths and weaknesses to address and respond to the opportunities and threats. So that the analysis results can be used as a basis for the development of mangrove forest tour in the village Langadai Kelumpang Hilir subdistrict in the future.            Based on the results of the assessment landscape mangrove forest tour in the village Langadai Kelumpang Hilir Subdistrict is in the range of 19-33 which means to have a high quality, so it has the potential to be developed as the natural attractions. Based on the results of this study resulted in several recommendations that include: Completing the supporting infrastructure of natural traveled activities such as: roads, bridges, gazebo, fishing, sanitary facilities, public toilets and others. Promotion to the public both in the region and outside the region. The government should  make the rules tight areas in the preservation of nature and fully supported by the community. Improving the quality of management of natural attractions integrated manner.